O evangelho no novo milênio: o uso da Web 2.0: uma parceria possível - Santos, Jackson (2010)
This research analyzes the use of Web 2.0 in the evangelical interrelationship. The approach is guided by the concern with the process of evangelization which involves mechanisms of cognition and faith that interfere in the individual s social living. Under this perspective, we aim to show that web 2.0 is a means that is in expansion contemporaneously, being a proactive mechanism in the process of evangelization. For this reason, its importance and applicability are highlighted. The established main goal of this research is the reflection concerning the means of media used in the process of going and taking God s word to all places (Matthew 28, 18-20). The huge difference that arises from this new opportunity for evangelism is the capacity to offer options in terms of space, actors/agents, time and flows, functioning as a new stage, enabling interactions at levels that were never thought before.